Acceptance of an assistive robot in older adults: a mixed-method study of human-robot interaction over a 1-month period in the Living Lab setting - Wu, Ya-Huei; Wrobel, Jérémy; Cornuet, Mélanie; Kerhervé, Hélène; Damnée, Souad; Rigaud, Anne-Sophie (Clinical interventions in aging, 2014)
There is growing interest in investigating acceptance of robots, which are increasingly being proposed as one form of assistive technology to support older adults, maintain their independence, and enhance their well-being. In the present study, we aimed to observe robot-acceptance in older adults, particularly subsequent to a 1-month direct experience with a robot. Six older adults with mild cognitive impairment (MCI) and five cognitively intact healthy (CIH) older adults were recruited. Participants interacted with an assistive robot in the Living Lab once a week for 4 weeks. After being shown how to use the robot, participants performed tasks to simulate robot use in everyday life. Mixed methods, comprising a robot-acceptance questionnaire, semistructured interviews, usability-performance measures, and a focus group, were used. Both CIH and MCI subjects were able to learn how to use the robot. However, MCI subjects needed more time to perform tasks after a 1-week period of not using the robot. Both groups rated similarly on the robot-acceptance questionnaire. They showed low intention to use the robot, as well as negative attitudes toward and negative images of this device. They did not perceive it as useful in their daily life. However, they found it easy to use, amusing, and not threatening. In addition, social influence was perceived as powerful on robot adoption. Direct experience with the robot did not change the way the participants rated robots in their acceptance questionnaire. We identified several barriers to robot-acceptance, including older adults' uneasiness with technology, feeling of stigmatization, and ethical/societal issues associated with robot use. It is important to destigmatize images of assistive robots to facilitate their acceptance. Universal design aiming to increase the market for and production of products that are usable by everyone (to the greatest extent possible) might help to destigmatize assistive devices.